PERANCANGAN SISTEM KONTROL BLYNK SMARTHOME DENGAN PEMBANGKIT LISTRIK TENAGA SURYA HIBRIDA BERBASIS PROGRAMMABLE LOGIC CONTROLLER - -, Juanita; Listiana, Reni (Jurnal Mahasiswa Terapan, 2024)
In the digital era, the demand for smart homes is increasing, particularly in the efficient and eco-friendly management of energy. This study discusses the design of a Blynk Smarthome control system that utilizes the ESP32 as the main controller to operate household appliances in a home equipped with a hybrid solar power plant. The system integrates PLC (Programmable Logic Controller)-based controlto optimize energy management from conventional electricity sources and solar power. The purpose of this study is to develop a control system that can monitor and manage the use of electrical appliances in real-time, enhance energy efficiency by utilizing hybrid electric power, and minimize operational costs through the use of Internet of Things (IoT) technology. Keywords: Blynk Smarthome, ESP32, PLC CP1E- NA20DR-A, Hybrid Solar Power Plant.